In-situ formed nanoscale Fe0 for fenton-like oxidation of thermosetting unsaturated polyester resin composites: Nondestructively recycle carbon fiber. (November 2022) - Wang, Baolong; Sun, Xueying; Lu, Fei; Shen, Yibo; Xu, Ningdi; Liu, Yingying; Huang, Yudong; Hu, Zhen
Abstract: Thermosetting unsaturated polyester resin (UPR) composites were found widespread industrial applications. However, the numerous stable carbon-carbon bonds in cross-linked networks made them intractable for degradation, causing the large-scale composite wastes. Here a nanoscale Fe 0 catalyst in-situ forming strategy was exploited to nondestructively recycle carbon fiber (CF) from UPR composites via Fenton-like reaction. The nano-Fe 0 catalyst employed in this strategy activated H2 O2 for removing UPR, featuring mild conditions and efficient degradation ability. Aiming at facile growth of the catalyst, a porous UPR was achieved by the hydrolysis of alkalic system. The nanoscale Fe 0 catalyst was subsequently formed in-situ on the surface of hydrolyzed resin by borohydride reduction. Benefiting from fast mass transfer, the in-situ grown nano-Fe 0 showed more efficient degradation ability than added nano-Fe 0 or Fe 2+ catalyst during Fenton-like reaction. The experiments indicated that hydrolyzed resin could be degraded more than 90% within 80 min, 80 °C. GC-MS, FT-IR analysis and Density functional theory (DFT) calculation were conducted to explained the fracture processes of carbon skeleton in hydrolyzed resin. Especially, a remarkable recovery process of CF from composites was observed, with a 100 percent elimination of resin. The recycled CF cloth exhibited a 99% strength retention and maintained the textile structure, microtopography, chemical structure, resulting in the nondestructive reclaim of CF. This in-situ formed nanoscale Fe 0 catalytic degradation strategy may provide a promising practical application for nondestructively recycle CF from UPR composites. Graphical abstract: Image 1 Highlights: More than 90 wt% of thermosetting UPR was degraded under 80 °C. The mild nano-Fe 0 in-situ forming strategy strongly improved degradation efficiency. The C=O in hydrolyzed resin was more easily attacked by radicals than aromatic ring because of the negative electric field potential. The CF cloth in UPR composites was nondestructively recycled.